Integrated Ratio of Metastatic to Examined Lymph Nodes and Number of Metastatic Lymph Nodes into the AJCC Staging System for Colon Cancer - Gao, Peng (Public Library of Science, 2012)
OBJECTIVE: At present, only the number of metastatic lymph nodes (LNs+) is used for the pN category of AJCC TNM system for colon cancer. Recently, the ratio of metastatic to examined lymph nodes (LNR) has been reported to represent powerful independent predictive capacity in colon cancer. We sought to propose a novel category (nLN) which intergrades LNR and LNs+ into the AJCC staging system for colon cancer. DESIGN: 34476 patients from the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) dataset with stage III colon cancer were reviewed. Harrell's C statistic was used to evaluate the predictive capacity. The Cox proportional hazards model was used to construct a novel category. RESULTS: The LNR category had more predictive capacity than the pN category in whole groups of patients (Harrell's C index: 0.6194 vs 0.6113, p = 0.003). Subgroup analysis showed that the LNR category was not better than pN category in predictive capacity if the number of lymph nodes examined was more than 13. We also found that there was significant survival heterogeneity among different pN categories at the same LNR category (P<0.001). The Harrell's C index for our nLN category which intergrades LNR and LNs+ was 0.6228, which was significant higher than that of the pN category (Harrell's C index: 0.6113, P<0.001) or LNR category (Harrell's C index: 0.6194, P = 0.005), respectively. CONCLUSION: To evaluate the prognosis of colon cancer, our nLN category which intergrades LNR with LNs+ is more accurate than the pN category or LNR category, respectively.